MIT MESJASZA W KSIĘGACH JAKUBOWYCH OLGI TOKARCZUK - Olędzka, Maria (Prace Polonistyczne, 2019)
Olga Tokarczuk’s The Books of Jacob tells the little-known story of the (pseudo-)Messiah, Jacob Leibovitz Frank. Yet the motif of the Messiah recurs in the novel also in other contexts. Apart from Jacob Frank, it features such characters as: Jesus Christ, Sabbata Zevi, Barukhia, and Eve Frank. With this in mind, the article analyzes the reader’s expectations connected with the figure of the Messiah, the representations of the myth of the Messiah in Tokarczuk’s novel, and the way in which salvation is defined in the text.